Do corporate governance motives drive hedge funds and private equity activities? - Ann-Kristin Achleitner; André Betzer; Jasmin Gider (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
We address the question of whether hedge fund and private equity investments in public firms are motivated by corporate governance improvements. As opposed to traditional financial investors both HF and PE are likely to have the incentives to alleviate agency conflicts. However, against the background of differences in their business models and organizational set ups, it remains an empirical question of whether they address the same or different agency conflicts. Studying HF and PE activities in a typical Continental European market like Germany promises to offer interesting insights about how HF and PE activities relate to the prevalence of family ownership, concentrated ownership structures and conflicts among majority and minority owners. We document empirical evidence that both HF and PE investments are driven by corporate governance improvements, but seem to address different types of agency conflicts. Whereas HF focus on firms with a lack of a controlling shareholder, in particular family shareholders, PE invest in firms which exhibit the potential to align manager-shareholder interests due to low managerial ownership. Both appear to address free cash flow problems differently. Aiming at dividend increases, HF tend use commitment devices that can be implemented over a short horizon. In contrast, PE are inclined to target firms which are particularly well-suited for a leverage increase because of low expected financial distress costs. This strategy requires a sufficiently long investment horizon.
Keywords: G34; 330; private equity; hedge funds; corporate governance; Private Equity; Hedgefonds; Corporate Governance; Aktienmarkt; Deutschland